A COMPARATIVE STUDY OF THE RELIGIOUS FILMS SANG PENCERAH AND SANG KIAI FROM THE PERSPECTIVE OF RELIGIOUS MODERATION - Achmad Zaki Ghufron; Widadi .; Luluk Fikri Zuhriyah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
This study conducts a comparative analysis of religious moderation values in two significant Indonesian Islamic biographical films: Sang Pencerah (2010) and Sang Kiai (2013). Using qualitative content analysis methodology, the research examines narrative structures, character development, dialogues, and visual symbolism to uncover how each film constructs its representation of moderate Islam. The findings reveal that while both films advocate for religious tolerance and anti-extremism, they employ distinct narrative approaches reflective of their historical contexts and protagonists' ideologies. Sang Pencerah presents KH. Ahmad Dahlan as a progressive reformer who combines Islamic teachings with modern education, emphasizing rational thinking and social inclusion. The film's cinematography, featuring bright lighting and open spaces, visually reinforces these themes of enlightenment and progress. Conversely, Sang Kiai portrays KH. Hasyim Asy'ari as a traditionalist leader who preserves religious values while fostering national unity during colonial occupation, using warm color palettes and pesantren settings to symbolize cultural resilience. The study highlights three key contributions: First, it demonstrates how religious moderation can be effectively communicated through popular media. Second, it reveals the complementary nature of reformist and traditionalist approaches to Islamic moderation. Third, it provides a framework for analyzing religious values in cultural products. These insights are particularly relevant for Indonesia's multicultural society and its current efforts to promote religious harmony through cultural means.